Soft magnetic powder, dust core, magnetic element, and electronic device

By optimizing the composition in the soft magnetic powder and using OES and EDX analysis technology to ensure that Cr is enriched in the amorphous phase and the B content is within a reasonable range, the problems of low density, easy oxidation and low correction of soft magnetic powder in the existing technology are solved. Solve the problem of coercivity and realize soft magnetic powder with high density, high magnetic permeability and low coercivity.

CN119340055APending Publication Date: 2025-01-21SEIKO EPSON CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410959901.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-19
Filing Date
2024-07-17
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The conventional soft magnetic powder is low in density and easy to oxidize when molding, and has insufficient low coercivity, making it difficult to produce molded bodies with excellent oxidation resistance, high density and magnetic permeability.

Method used

The composition calculated using a solid-state optical emission spectrometer (OES) is represented by FexCuaNbb(Si1-y(B1-zCrz)y)100-x-a-b, which satisfies a specific atomic number ratio range and is analyzed by an energy-dispersive fluorescence X-ray analyzer ( EDX) optimizes the composition of the amorphous phase and the crystalline phase to ensure that Cr is enriched in the amorphous phase and the B content is within a reasonable range to achieve the stabilization of the amorphous phase and the refinement of the crystalline phase.

Benefits of technology

The oxidation resistance and magnetic permeability of the soft magnetic powder are improved, the compact powder body with high density is formed, the coercive force is reduced, and the manufacturing process is relatively simple.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340055A_ABST
    Figure CN119340055A_ABST
Patent Text Reader

Abstract

The invention provides a soft magnetic powder, a powder magnetic core, a magnetic element, and an electronic device. The composition of the soft magnetic powder is represented by FexCuaNbb (Si1-y (B1-zCrz) y) 100-x-a-b (where a, b, x, y, and z satisfy 0.3 < = a < = 2.0, 2.0 < = b < = 4.0, 75.5 < = x < = 79.5, 0.55 < = y < = 0.91, and 0.015 < = z < = 0.185), the soft magnetic powder has an amorphous phase and a crystalline phase, and when the Cr content calculated by OES is X (Cr) and the Cr content and B content of the amorphous phase calculated by EDX are Y (Cr) and Y (B), the soft magnetic powder satisfies formula (1) and formula (2): X (Cr) < Y (Cr) < = X (Cr) + 1.0 and 3.0 < = Y (B) < = 15.0 (2).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to soft magnetic powder, pressed powder magnetic core, magnetic element and electronic equipment. Background Art

[0002] In order to achieve miniaturization and high output in various mobile devices equipped with magnetic components including powder cores, it is necessary to cope with high frequencies and strong currents of switching frequencies of switching power supplies. Accordingly, the soft magnetic powder contained in the powder cores is also required to cope with high frequencies and strong currents.

[0003] Patent Document 1 discloses a soft magnetic powder characterized by having a x Cu a Nb b (Si 1-y B y ) 100-x-a-b The composition represented by , wherein a, b and x are respectively expressed in atomic % and satisfy 0.3≤a≤2.0, 2.0≤b≤4.0 and 73.0≤x≤79.5. In addition, y is a value satisfying f(x)≤y<0.99. It should be noted that f(x)=(4×10 -34 )x 17.56 The soft magnetic powder contains more than 30% by volume of a crystalline structure having a particle size of 1.0 nm or more and 30.0 nm or less. Such a soft magnetic powder can achieve a magnetic element with high magnetic permeability and miniaturization. In addition, such a soft magnetic powder contains tiny crystals, so it can achieve low iron loss in the high frequency range.

[0004] Patent Document 1: Japanese Patent Application Publication No. 2019-189928

[0005] However, the soft magnetic powder described in Patent Document 1 has the following technical problems: it is easily oxidized due to its composition and the density during molding cannot be sufficiently increased. The density of the molded body affects the magnetic permeability of the magnetic element having a pressed powder magnetic core. Therefore, it is a technical problem to realize a soft magnetic powder that can produce a molded body with excellent oxidation resistance and high density and magnetic permeability.

[0006] In order to achieve low iron loss in a high frequency range, it is important to reduce the coercive force that causes hysteresis loss. However, the soft magnetic powder described in Patent Document 1 is not sufficiently low in coercive force.

[0007] Furthermore, it is disclosed that in the soft magnetic powder described in Patent Document 1, an amorphous structure and a tiny crystalline structure are mixed. In order to realize such a structure, after manufacturing a powder occupied by an amorphous structure, it is necessary to heat treat the powder to partially crystallize it. However, in the soft magnetic powder described in Patent Document 1, the coercive force after heat treatment is likely to change depending on the conditions of the heat treatment. Therefore, it has become a technical problem to efficiently manufacture a soft magnetic powder that realizes low coercive force.

[0008] Therefore, a technical problem is to realize a soft magnetic powder that can produce a powder compact having high density and magnetic permeability and has low coercive force and is easy to produce. Summary of the invention

[0009] The composition of the soft magnetic powder according to the application example of the present invention obtained by solid emission spectrometry (OES) is represented by the composition formula in terms of atomic ratio: Fe x Cu a Nb b (Si 1-y (B 1-z Cr z ) y ) 100-x-a-b wherein a, b, x, y, and z satisfy 0.3≤a≤2.0, 2.0≤b≤4.0, 75.5≤x≤79.5, 0.55≤y≤0.91, and 0.015≤z≤0.185, and the soft magnetic powder comprises an amorphous phase composed of an amorphous structure in which Fe is the highest concentration element, and a crystalline phase composed of a crystalline structure in which Fe is the highest concentration element, and when the Cr content [atomic %] determined by OES is X(Cr), and the Cr content [atomic %] and the B content [atomic %] of the amorphous phase determined by an energy dispersive X-ray fluorescence analyzer (EDX) are Y(Cr) and Y(B), the following formulas (1) and (2) are satisfied:

[0010] X(Cr)<Y(Cr)≤X(Cr)+1.0 (1),

[0011] 3.0≤Y(B)≤15.0 (2).

[0012] A powder magnetic core according to an application example of the present invention includes the soft magnetic powder according to an application example of the present invention.

[0013] A magnetic element according to an application example of the present invention includes the powder magnetic core according to the application example of the present invention.

[0014] An electronic device according to an application example of the present invention includes the magnetic element according to the application example of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is a schematic diagram of an observed image obtained by enlarging and observing a cross section of a particle of the soft magnetic powder according to the embodiment.

[0016] Figure 2 It is a plan view schematically showing a ring-shaped coil component.

[0017] Figure 3 It is a perspective view schematically showing a closed-circuit type coil component.

[0018] Figure 4 It is a perspective view showing the structure of a mobile personal computer as an electronic device including the magnetic element according to the embodiment.

[0019] Figure 5 It is a plan view showing the structure of a smartphone as an electronic device including the magnetic element according to the embodiment.

[0020] Figure 6 It is a perspective view showing the structure of a digital still camera as an electronic device including the magnetic element according to the embodiment.

[0021] Description of Reference Numerals

[0022] 1: particle; 2: amorphous phase; 3: crystalline phase; 6: Cu segregation phase; 10: coil component; 11: pressed powder core; 12: wire; 20: coil component; 21: pressed powder core; 22: wire; 100: display unit; 1000: magnetic element; 1100: personal computer; 1102: keyboard; 1104: main body; 1106: display unit; 1200: smart phone; 1202: operation button; 1204: answering port; 1206: speaking port; 1300: digital still camera; 1302: housing; 1304: light receiving unit; 1306: shutter button; 1308: memory. DETAILED DESCRIPTION

[0023] Hereinafter, the soft magnetic powder, the powder magnetic core, the magnetic element and the electronic device of the present invention will be described in detail based on the preferred embodiments shown in the drawings.

[0024] 1. Soft magnetic powder

[0025] The soft magnetic powder according to the embodiment is a powder exhibiting soft magnetism and can be used for any purpose, for example, by bonding particles to each other via a binder to produce various powder bodies such as powder cores and electromagnetic wave absorbers.

[0026] 1.1. Brief Introduction of Soft Magnetic Powder

[0027] The composition of the soft magnetic powder according to the embodiment determined by a solid emission spectrometer (OES) is represented by the composition formula Fe x Cu a Nb b (Si 1-y (B 1-z Cr z ) y ) 100-x-a-b Indicates that a, b, x, y, and z satisfy 0.3≤a≤2.0, 2.0≤b≤4.0, 75.5≤x≤79.5, 0.55≤y≤0.91, and 0.015≤z≤0.185.

[0028] Solid state emission spectrometer is a device that performs chemical analysis on a sample that has been dissolved by pretreatment of soft magnetic powder, and quantifies the concentration of each element. Therefore, the composition obtained by OES can be called the composition of the entire soft magnetic powder.

[0029] Examples of the pretreatment include various pretreatments specified in JIS G 1258-0: 2017, JIS G 1258-1: 2014, JIS G 1258-2: 2014, JIS G 1258-3: 2014, JIS G 1258-4: 2007, JIS G 1258-5: 2007, JIS G 1258-6: 2007, JIS G 1258-7: 2007, and JIS G 1258-8: 2017.

[0030] Figure 1 1 is a schematic diagram of an observation image obtained by enlarging and observing a cross section of a particle 1 of the soft magnetic powder according to the embodiment. Figure 1 It is a partial enlarged view of the cross section of a particle 1.

[0031] Figure 1 The particle 1 shown has an amorphous phase 2 composed of an amorphous structure and a crystalline phase 3 composed of a crystalline structure. Figure 1 As shown, in the particle 1, the amorphous phase 2 is a matrix, and the granular crystal phase 3 is dispersed in the matrix.

[0032] The amorphous phase 2 is composed of an amorphous structure in which Fe is the highest concentration of the constituent element. In addition, the crystalline phase 3 is composed of a crystalline structure in which Fe is the highest concentration of the constituent element. It should be noted that the particle 1 may also contain other phases besides the amorphous phase 2 and the crystalline phase 3. Examples of other phases include: Figure 1 The Cu segregation phase 6 shown.

[0033] Here, the Cr content [atomic %] obtained by OES is referred to as X(Cr), and the Cr content [atomic %] and B content [atomic %] of the amorphous phase 2 obtained by an energy dispersive X-ray fluorescence analyzer (EDX) are referred to as Y(Cr) and Y(b). At this time, the soft magnetic powder according to the embodiment satisfies the following formulas (1) and (2).

[0034] X(Cr)<Y(Cr)≤X(Cr)+1.0 (1),

[0035] 3.0≤Y(B)≤15.0 (2).

[0036] In such a soft magnetic powder, Cr is added to the existing five elements of Fe, Cu, Nb, Si and B, and the amount of addition is optimized. Moreover, Cr is enriched in the amorphous phase 2. Specifically, as shown in the above formula (1), the Cr content in the amorphous phase 2 obtained by EDX is higher than the Cr content of the entire powder obtained by OES. In addition, the amorphous phase 2 contains B in a predetermined content. Specifically, as shown in the above formula (2), the B content in the amorphous phase 2 obtained by EDX is within a predetermined range.

[0037] According to the above-mentioned configuration, the oxidation resistance of the soft magnetic powder can be improved. As a result, when the soft magnetic powder is pressed, the density of the pressed powder can be suppressed from decreasing due to the oxides. As a result, the magnetic permeability of the pressed powder can be improved.

[0038] In addition, in the soft magnetic powder according to the embodiment, the Cr-rich amorphous phase 2 is stabilized and the coarsening of the crystalline phase 3 is suppressed. Therefore, the soft magnetic powder according to the embodiment can have a low coercive force. It should be noted that the stabilization of the amorphous phase 2 means that the amorphous phase 2 becomes easy to maintain the amorphous state.

[0039] Moreover, in order to make the amorphous phase 2 and the crystalline phase 3 coexist, after manufacturing the powder occupied by the amorphous phase 2, it is necessary to perform heat treatment (crystallization treatment) to partially crystallize it. In this case, depending on the conditions of the crystallization treatment, the particle size (crystal particle size) of the crystalline phase 3 is prone to change, which may lead to the generation of a coarse crystalline phase 3. The coarse crystalline phase 3 will cause an increase in coercivity. In view of this, in the soft magnetic powder involved in the embodiment, due to the addition of a predetermined concentration of Cr, the stabilization of the amorphous phase 2 can be easily achieved. As a result, regardless of the conditions of the crystallization treatment, it is easy to suppress the coarsening of the crystalline phase 3. That is, according to the above-mentioned structure, for example, it is not necessary to perform such operations as significantly increasing the heating rate to prevent excessive crystallization, and it is also easy to achieve low coercivity. Therefore, the soft magnetic powder involved in this embodiment can be said to be easy to manufacture.

[0040] In the soft magnetic powder according to the embodiment, it is preferable that the crystal grain size measured by X-ray diffraction is 20.0 nm or less. This can sufficiently reduce the coercivity of the soft magnetic powder.

[0041] Next, the soft magnetic powder according to the embodiment will be described in detail.

[0042] 1.2. Composition

[0043] As described above, the soft magnetic powder according to the embodiment has a composition obtained by OES, that is, a composition represented by the composition formula consisting of Fe, Cu, Nb, Si, and B as described above.

[0044] Fe (iron) greatly affects the basic magnetic properties and mechanical properties of the soft magnetic powder according to the embodiment.

[0045] The Fe content x is 75.5 atomic % or more and 79.5 atomic % or less, but preferably 76.0 atomic % or more and 78.5 atomic % or less, and more preferably 76.5 atomic % or more and 78.0 atomic % or less. It should be noted that if the Fe content x is lower than the lower limit, the saturation magnetic flux density of the soft magnetic powder decreases. On the other hand, if the Fe content x is higher than the upper limit, an amorphous structure cannot be stably formed when manufacturing the soft magnetic powder, so the crystal grain size becomes too large, resulting in an increase in coercive force.

[0046] Cu (copper) tends to separate from Fe when the soft magnetic powder involved in the embodiment is manufactured from raw materials. Therefore, the composition becomes unstable due to the inclusion of Cu, and a region that is easy to be locally crystallized is generated in the particle 1. As a result, the precipitation of the Fe phase of the body-centered cubic lattice that is easy to crystallize is promoted, and it becomes easy to form a crystalline phase having a crystal grain size as described above.

[0047] The content a of Cu is 0.3 atomic % or more and 2.0 atomic % or less, but preferably 0.5 atomic % or more and 1.5 atomic % or less, and more preferably 0.7 atomic % or more and 1.3 atomic % or less. It should be noted that if the content a of Cu is lower than the lower limit, the refinement of the crystalline phase is destroyed. On the other hand, if the content a of Cu is higher than the upper limit, the mechanical properties of the soft magnetic powder are reduced, which may lead to brittleness.

[0048] When Nb (niobium) is heat-treated from a state in which it occupies the amorphous structure, it contributes to the refinement of the crystal phase 3 together with Cu. Therefore, the crystal phase 3 having the above-mentioned crystal grain size is easily formed.

[0049] The content b of Nb is 2.0 atomic % or more and 4.0 atomic % or less, but preferably 2.5 atomic % or more and 3.5 atomic % or less, and more preferably 2.7 atomic % or more and 3.3 atomic % or less. It should be noted that if the content b of Nb is lower than the lower limit, the refinement of the crystalline phase 3 is destroyed. On the other hand, if the content b of Nb is higher than the upper limit, the mechanical properties of the soft magnetic powder are reduced and it may become brittle. In addition, the magnetic permeability of the soft magnetic powder is reduced.

[0050] Si (silicon) promotes amorphization when manufacturing the soft magnetic powder involved in the embodiment from raw materials. Therefore, when manufacturing the soft magnetic powder involved in the embodiment, a homogeneous amorphous structure is initially formed, and then by crystallizing it, it becomes easy to form a crystalline phase 3 with a more uniform crystal grain size. The uniform crystal grain size helps to average the magnetocrystalline anisotropy in each crystalline phase 3, so it can reduce the coercive force and increase the magnetic permeability, which helps to improve the soft magnetic properties.

[0051] B (boron) promotes amorphization when manufacturing the soft magnetic powder involved in the embodiment from raw materials. Therefore, when manufacturing the soft magnetic powder involved in the embodiment, a homogeneous amorphous structure is initially formed, and then by crystallizing it, it becomes easy to form a crystalline phase 3 with a more uniform crystal grain size. As a result, the coercive force can be reduced, and the magnetic permeability can be increased, and the improvement of soft magnetism can be achieved. In addition, by using Si and B in combination, based on the difference in atomic radius between the two, amorphization can be promoted in a complementary manner.

[0052] Cr (chromium) is enriched in the amorphous phase 2, thereby contributing to the stabilization of the amorphous phase 2. By stabilizing the amorphous phase 2, the coarsening of the crystalline phase 3 is suppressed, and the uniformity of the crystal grain size is achieved. As a result, the low coercivity of the soft magnetic powder can be achieved. In addition, Cr improves the oxidation resistance of the soft magnetic powder. As a result, when the soft magnetic powder is pressed, the decrease in the density of the pressed powder can be suppressed by the oxide. As a result, the magnetic permeability and saturation flux density measured in the state of the pressed powder can be improved.

[0053] Here, the total content of Si, B and Cr (Si+B+Cr) is set to 1, and the ratio of the total content of B and Cr (B+Cr) to the total content (Si+B+Cr) is set to y.

[0054] The y satisfies 0.55≤y≤0.91, but preferably satisfies 0.60≤y≤0.90, and more preferably satisfies 0.65≤y≤0.80. Thus, a balance can be achieved between the amounts of Si, B, and Cr. As a result, the coercivity of the soft magnetic powder can be reduced, and both oxidation resistance and magnetic permeability can be better balanced.

[0055] It should be noted that if y is lower than the lower limit, the amorphous phase 2 becomes unstable and becomes difficult to reduce the coercivity. In addition, the oxidation resistance is reduced, and the crystal grain size becomes too small, and the magnetic permeability is reduced. On the other hand, if y is higher than the upper limit, the Si concentration is reduced, so it becomes difficult to form the amorphous phase 2.

[0056] In addition, the ratio of the Cr content to the total content (B+Cr) is represented by z.

[0057] This z satisfies 0.015≤z≤0.185, but preferably satisfies 0.030≤z≤0.150, and more preferably satisfies 0.045≤z≤0.120. Thus, a balance between the amounts of B and Cr can be achieved. As a result, while achieving a lower coercivity of the soft magnetic powder, both oxidation resistance and magnetic permeability can be better balanced.

[0058] It should be noted that if z is lower than the lower limit, it becomes difficult to reduce the coercivity. In addition, the oxidation resistance is reduced, and the crystal grain size becomes too small, and the magnetic permeability is reduced. On the other hand, if z is higher than the upper limit, the B concentration is reduced, so it becomes difficult to form the amorphous phase 2.

[0059] It should be noted that the Si content is preferably 1.5 atomic % to 14.0 atomic %, more preferably 3.0 atomic % to 10.0 atomic %, and even more preferably 4.0 atomic % to 8.0 atomic %. This can further increase the magnetic permeability of the soft magnetic powder and further reduce the coercive force.

[0060] The B content is preferably 5.0 atomic % to 17.0 atomic %, more preferably 7.0 atomic % to 16.0 atomic %, and even more preferably 9.0 atomic % to 13.5 atomic %. This can further increase the magnetic permeability of the soft magnetic powder and further reduce the coercive force.

[0061] In addition, the Cr content is preferably 0.3 atomic % or more and 2.7 atomic % or less, more preferably 0.5 atomic % or more and 2.2 atomic % or less, and further preferably 0.8 atomic % or more and 1.8 atomic % or less. Thus, the oxidation resistance of the soft magnetic powder can be further improved, and the generation of oxides can be suppressed to a lesser extent. As a result, the decrease in the density of the powder compact accompanied by the oxides can be suppressed, and the magnetic permeability and saturation magnetic flux density of the powder compact can be further improved. In addition, the crystal grain size of the crystalline phase 3 can be accurately controlled, and the balance between low coercive force and high magnetic permeability can be further optimized.

[0062] The soft magnetic powder according to the embodiment has the composition formula Fe x Cu a Nb b(Si 1-y (B 1-z Cr z ) y ) 100-x-a-b In addition to the composition represented, impurities may also be included. As impurities, any element other than the above may be listed, and preferably the total content of the impurities is less than 0.50 atomic %. If within this range, even if impurities are mixed in, the above effects are not easily hindered, so it is allowed to contain intentionally added elements and unavoidably mixed elements.

[0063] In addition, the content of each element contained in the impurities is preferably 0.05 atomic % or less. Within this range, the impurities are not likely to hinder the above-mentioned effects, and therefore the impurities are allowed to be contained.

[0064] Among the impurities, the oxygen content is preferably 1500 ppm or less, and more preferably 800 ppm or less. When the oxygen content is within the above range, the generation of oxides that reduce the density of the powder compact can be suppressed to a particularly low level.

[0065] The soft magnetic powder according to the embodiment is described above, but the composition and impurities are determined by a solid emission spectrometer (OES), such as SPECTRO LAB M9 manufactured by SPECTRO and QSN750 manufactured by OBLF.

[0066] In addition, impurities can be detected by the following analytical means as needed. Examples of analytical means include: iron and steel-atomic absorption spectrometry specified in JIS G 1257:2000, iron and steel-ICP emission spectrometry specified in JIS G 1258:2007, iron and steel-spark discharge emission spectrometry specified in JIS G1253:2002, iron and steel-fluorescent X-ray analysis specified in JIS G 1256:1997, and weight-titration-absorptiometry specified in JIS G 1211 to G 1237.

[0067] When C (carbon) and S (sulfur) are particularly specified, the oxygen stream combustion (high frequency induction heating furnace combustion)-infrared absorption method specified in JIS G 1211:2011 may be used. Specifically, for example, a carbon-sulfur analyzer, CS-200, manufactured by LECO Corporation may be used.

[0068] In addition, when N (nitrogen) and O (oxygen) are particularly specified, the nitrogen quantitative method for iron and steel specified in JIS G 1228:1997 and the oxygen quantitative method general rules for metal materials specified in JIS Z 2613:2006 can also be used. Specifically, the oxygen-nitrogen analyzer TC-300 / EF-300 manufactured by LECO and the oxygen-nitrogen-hydrogen analyzer ONH836 manufactured by LECO can be mentioned.

[0069] 1.3. Amorphous phase

[0070] The amorphous phase 2 is composed of an amorphous structure in which Fe is the highest concentration of the constituent element. The amorphous phase 2 and the crystalline phase 3 can be distinguished based on whether B is enriched. If the cross section of the particle 1 is subjected to an element mapping analysis based on EDX, it is possible to distinguish between an area where B is enriched and an area where the concentration of B is lower than that of the area. The former area can be regarded as the amorphous phase 2, and the latter area can be regarded as the crystalline phase 3. It should be noted that enrichment means a state in which the concentration of B is higher than the surrounding area. For example, in the B concentration distribution obtained by element mapping analysis, the area with a high concentration of B is represented by color density, etc.

[0071] As described above, Cr is enriched in the amorphous phase 2. Therefore, as described above, by enriching Cr, the amorphous phase 2 is stabilized and the coarsening of the crystalline phase 3 is suppressed. In addition, Cr is enriched in the amorphous phase 2, so that it is considered that a blocking effect of suppressing the growth of crystals can be produced, and it is considered that the coarsening of the crystalline phase 3 can also be suppressed by this blocking effect.

[0072] If the cross section of the particle 1 is subjected to elemental analysis based on EDX, the concentrations of each element in the amorphous phase 2 and the crystalline phase 3 can be obtained. The Cr content Y (Cr) [atomic %] of the amorphous phase 2 obtained by EDX and the Cr content X (Cr) [atomic %] obtained by OES satisfy the relationship represented by the following formula (1):

[0073] X(Cr)<Y(Cr)≤X(Cr)+1.0 (1).

[0074] It should be noted that if the Cr content Y(Cr) of the amorphous phase 2 is lower than the lower limit, it can be said that Cr is not sufficiently enriched in the amorphous phase 2. In this case, the stabilization of the amorphous phase 2 cannot be fully achieved, and the coarsening of the crystalline phase 3 cannot be fully suppressed. On the other hand, if the Cr content Y(Cr) of the amorphous phase 2 is higher than the upper limit, Cr becomes excessively enriched in the amorphous phase 2, and the amorphous structure becomes unstable instead.

[0075] It should be noted that the lower limit of Y(Cr) is preferably X(Cr)+0.1 or more, more preferably X(Cr)+0.2 or more, and further preferably 1.5 or more. On the other hand, the upper limit of Y(Cr) is preferably X(Cr)+0.8 or less, more preferably X(Cr)+0.6 or less, and further preferably 2.5 or less.

[0076] The Cr content Y(Cr) of the amorphous phase 2 is an average value of the Cr contents measured at five or more locations in the amorphous phase 2 included in the cross section of one particle 1 .

[0077] In addition, the concentration of B is optimized in the amorphous phase 2. This can increase the crystallization temperature and facilitate the formation of the amorphous phase 2. That is, B with an optimized concentration contributes to the stabilization of the amorphous phase 2.

[0078] The B content Y(B) [atomic %] of the amorphous phase 2 determined by EDX satisfies the relationship represented by the following formula (2):

[0079] 3.0≤Y(B)≤15.0 (2).

[0080] It should be noted that if the B content Y(B) of the amorphous phase 2 is lower than the lower limit, it can be said that B is not sufficiently present in the amorphous phase 2. In this case, the stabilization of the amorphous phase 2 cannot be fully achieved, and the coarsening of the crystalline phase 3 cannot be fully suppressed. On the other hand, if the B content Y(B) of the amorphous phase 2 is higher than the upper limit, B is excessively present in the amorphous phase 2, and the amorphous structure becomes unstable instead.

[0081] It should be noted that the lower limit of Y(B) is preferably 4.0 or more, and more preferably 4.5 or more. On the other hand, the upper limit of Y(B) is preferably 10.0 or less, and more preferably 7.0 or less.

[0082] The B content Y(B) of the amorphous phase 2 is an average value of the B contents measured at five or more locations in the amorphous phase 2 included in the cross section of one particle 1 .

[0083] The Fe content in the amorphous phase 2 is preferably 50.0 atomic % or more, more preferably 70.0 atomic % or more and 95.0 atomic % or less, and further preferably 80.0 atomic % or more and 90.0 atomic % or less.

[0084] Furthermore, the Si content in the amorphous phase 2 is preferably 2.0 atomic % or more and 8.0 atomic % or less, more preferably 3.0 atomic % or more and 7.0 atomic % or less, and further preferably 4.0 atomic % or more and 6.0 atomic % or less.

[0085] 1.4. Crystalline phase

[0086] The crystal phase 3 is composed of a crystal structure in which Fe is the highest concentration constituent element. As shown in the following formula (3), the Cr content Z (Cr) [atomic %] of the crystal phase 3 obtained by EDX and the Cr content X (Cr) obtained by OES preferably satisfy the relationship represented by the following formula (3).

[0087] Z(Cr)<X(Cr) (3)

[0088] Since Cr is concentrated in the amorphous phase 2, the Cr content in the crystalline phase 3 tends to decrease. Therefore, by satisfying the above formula (3), the amorphous phase 2 can be further stabilized. It should be noted that if the Cr content Z(Cr) of the crystalline phase 3 is higher than the upper limit, the crystalline phase 3 may not be composed of a stable crystalline structure. In this case, it may be difficult to fully increase the magnetic permeability of the soft magnetic powder.

[0089] It should be noted that the lower limit of Z(Cr) may not be particularly set, but is preferably 0.3 or more, more preferably 0.5 or more, and further preferably 0.8 or more. On the other hand, the upper limit of Z(Cr) is preferably X(Cr)-0.1 or less, more preferably X(Cr)-0.2 or less, and further preferably 2.0 or less.

[0090] The Cr content Z(Cr) of the crystal phase 3 is an average value of the Cr contents measured at five or more locations in the crystal phase 3 included in the cross section of one particle 1 .

[0091] The Fe content in the crystal phase 3 is preferably 50.0 atomic % or more, more preferably 70.0 atomic % or more and 95.0 atomic % or less, and further preferably 80.0 atomic % or more and 90.0 atomic % or less.

[0092] Furthermore, the Si content in the crystal phase 3 is preferably 3 atomic % or more and 9 atomic % or less, more preferably 4 atomic % or more and 8 atomic % or less, and further preferably 5 atomic % or more and 7 atomic % or less.

[0093] The amorphous phase 2 and the crystalline phase 3 are described above, and the above-mentioned contents are obtained by an energy dispersive X-ray fluorescence analyzer (EDX). Examples of energy dispersive X-ray fluorescence analyzers include NSS7 manufactured by Thermo Fisher Scientific. It should be noted that the acceleration voltage during the analysis was set to 120 kV, and Cliff-Lorimer (MBTS) without absorption correction was used as the quantitative means of the EDX spectrum.

[0094] 1.5. Crystal size

[0095] The crystal particle size of the soft magnetic powder involved in the embodiment measured by X-ray diffraction method is preferably less than 20.0nm, more preferably more than 3.0nm and less than 15.0nm, and further preferably more than 6.0nm and less than 13.0nm. If the crystal particle size is within such a range, the crystal particle size of the soft magnetic powder is optimized, so the magnetic permeability of the soft magnetic powder can be improved. In addition, the magnetocrystalline anisotropy in each crystalline phase 3 is easily averaged, and a soft magnetic powder with low coercive force can be obtained. Moreover, by making the magnetic permeability higher, it becomes difficult to saturate even under strong current, so it becomes easy to increase the saturation flux density of the soft magnetic powder.

[0096] The crystal grain size determination based on the X-ray diffraction method is performed by obtaining X-ray diffraction patterns for the soft magnetic powder and the standard sample, estimating the diffraction line width originating from Fe, and then calculating the crystal grain size by the Scherrer method. The X-ray diffraction pattern obtained for the standard sample is used to estimate the diffraction line width originating from the device. The crystal grain size calculated from the soft magnetic powder (tested sample) can be corrected by the diffraction line width.

[0097] 1.6. Various features

[0098] The average particle size of the soft magnetic powder involved in the embodiment is not particularly limited, and is preferably 1 μm or more and 50 μm or less, more preferably 10 μm or more and 45 μm or less, and further preferably 20 μm or more and 40 μm or less. By using a soft magnetic powder with such an average particle size, the path through which the eddy current flows can be shortened, so that a magnetic element that can fully suppress the eddy current loss generated in the particles of the soft magnetic powder can be manufactured. In addition, the filling rate of the soft magnetic powder in the powder compact can be increased, and the magnetic permeability and saturation flux density of the powder core can be increased.

[0099] When the average particle size of the soft magnetic powder is 10 μm or more, a higher compact density can be achieved by mixing with a soft magnetic powder having a smaller average particle size than the soft magnetic powder of the embodiment. This makes it easier to further increase the saturation magnetic flux density and magnetic permeability of the powder core.

[0100] The average particle size of the soft magnetic powder refers to a particle diameter D50 at which the cumulative frequency from the small diameter side reaches 50% in the volume-based cumulative particle size distribution of the soft magnetic powder obtained using a laser diffraction particle size distribution analyzer.

[0101] If the average particle size of the soft magnetic powder is lower than the lower limit, the soft magnetic powder becomes too fine, and the filling property of the soft magnetic powder may become easily reduced. As a result, the molding density of the powder core is reduced, so according to the composition and mechanical properties of the soft magnetic powder, the magnetic permeability and saturation flux density of the powder core may be reduced. On the other hand, if the average particle size of the soft magnetic powder is higher than the upper limit, according to the composition and mechanical properties of the soft magnetic powder, the eddy current loss generated in the particles cannot be fully suppressed, and the iron loss of the magnetic element may increase.

[0102] The coercive force of the soft magnetic powder involved in the embodiment is not particularly limited, and is preferably less than 2.00 [Oe] (less than 160 [A / m]), more preferably 0.10 [Oe] or more and 1.67 [Oe] or less (39.9 [A / m] or more and 133 [A / m] or less), and further preferably 0.10 [Oe] or more and 1.00 [Oe] or less (39.9 [A / m] or more and 79.6 [A / m] or less). In this way, by using a soft magnetic powder with low coercive force, a magnetic element that can fully suppress hysteresis loss even at high frequencies can be manufactured. It should be noted that the coercive force can also be lower than the lower limit, but this may increase the difficulty of manufacturing.

[0103] The coercive force of the soft magnetic powder can be measured by, for example, a vibrating sample magnetometer such as TM-VSM1230-MHHL manufactured by Tamagawa Seisakusho Co., Ltd.

[0104] The magnetic permeability of the soft magnetic powder involved in the embodiment when made into a powder compact is preferably 24.0 or more, and more preferably 25.0 or more at a measuring frequency of 1 MHz. Such soft magnetic powder has excellent DC superposition characteristics and high electromagnetic conversion efficiency at high frequencies, which helps to achieve miniaturized magnetic components. It should be noted that the magnetic permeability is 24.0 or more when the epoxy resin is added at a ratio of 2% by mass to the soft magnetic powder and the molding pressure is 294 MPa (3t / cm 2 ) was pressed into a ring shape with an outer diameter of 14 mm, an inner diameter of 8 mm, and a thickness of 3 mm under 40 °C. The ring-shaped pressed powder was then wound with a wire of 0.6 mm in diameter seven times for measurement. The magnetic permeability was measured using an impedance analyzer such as 4194A manufactured by Agilent Technologies, Inc. The measurement frequency was set to 1 MHz.

[0105] The saturation magnetic flux density of the soft magnetic powder according to the embodiment is preferably 1.25 [T] or more, and more preferably 1.30 [T] or more. This makes it possible to obtain a magnetic element that is not easily saturated even under a high current.

[0106] The saturation magnetic flux density of the soft magnetic powder can be measured, for example, by the following method.

[0107] First, the true density ρ of the soft magnetic powder was measured by a fully automatic gas displacement densitometer, AccuPyc1330 manufactured by Micromeritics. Then, the maximum magnetization Mm of the soft magnetic powder was measured by a vibrating sample magnetometer, VSM system, TM-VSM1230-MHHL manufactured by Tamagawa Seisakusho Co., Ltd. And the saturation magnetic flux density Bs was calculated by the following formula,

[0108] Bs = 4π / 10000×ρ×Mm.

[0109] The soft magnetic powder according to the embodiment is mixed with 2 mass % of epoxy resin, and the obtained mixture is press-formed at a pressure of 294 MPa. The density of the obtained powder compact is preferably 4.99 g / cm 3 More preferably, 5.01 g / cm 3 Above and 5.20g / cm 3 If the density of the powder compact is within the above range, the occupancy rate of oxides in the powder compact is sufficiently suppressed, and as a result, the occupancy rate of alloys can be sufficiently ensured. As a result, the magnetic permeability and saturation magnetic flux density of the magnetic element can be further improved.

[0110] It should be noted that the soft magnetic powder according to the embodiment may be mixed with other soft magnetic powders or non-soft magnetic powders to form mixed powders for various purposes.

[0111] 2. Method for producing soft magnetic powder

[0112] Next, an example of a method for producing the soft magnetic powder will be described.

[0113] The soft magnetic powder can be a powder produced by any method. As an example of a production method, for example, in addition to various atomization methods such as water atomization, gas atomization, and rotating water flow atomization, a pulverization method and the like can also be cited. Among them, the atomization method is preferably used. According to the atomization method, the particle shape is closer to a true sphere and the formation of oxides and the like is less, and high-quality metal powder can be effectively produced. Therefore, a metal powder with a smaller specific surface area can be produced by the atomization method.

[0114] Atomization is a method of producing metal powder by causing a high-speed jet of liquid or gas to impact molten metal, causing the molten metal to be finely powdered and then cooled. In the atomization method, the molten metal is finely powdered and then sphericalized during the solidification process, so particles that are closer to a true sphere can be produced.

[0115] Among them, the water atomization method is a method of producing metal powder from molten metal by using a liquid such as water as a coolant, spraying it in an inverted cone shape that converges to a point, and causing molten metal to flow down to the convergence point and be impacted.

[0116] In addition, the rotating water flow atomization method is a method of producing metal powder by supplying coolant along the inner circumference of a cooling cylinder to rotate along the inner circumference, and spraying liquid or gas spray onto molten metal on the other hand, and taking the scattered molten metal into the coolant.

[0117] Furthermore, the gas atomization method is a method of producing metal powder from molten metal by using gas (gas) as a coolant, spraying it in an inverted cone shape that converges to one point, and causing molten metal to flow down to the convergence point and be impacted.

[0118] Each particle of the metal powder thus obtained is composed of an amorphous structure. By subjecting such metal powder to a crystallization treatment (heat treatment), the amorphous structure is partially crystallized. Thus, a soft magnetic powder containing the aforementioned amorphous phase 2 and crystalline phase 3 is obtained.

[0119] The temperature of the crystallization treatment is not particularly limited, and is preferably 520°C or more and 640°C or less, more preferably 530°C or more and 630°C or less, and further preferably 540°C or more and 620°C or less. In addition, regarding the time of the heat treatment, the time maintained at the temperature is preferably set to 1 minute or more and 180 minutes or less, more preferably 3 minutes or more and 120 minutes or less, and further preferably 5 minutes or more and 60 minutes or less. By setting the temperature and time of the heat treatment within the range, respectively, a crystalline phase 3 having a uniform crystal grain size within an accurate range can be generated.

[0120] It should be noted that if the temperature or time of the heat treatment is lower than the lower limit, crystallization becomes insufficient, which may result in too small a crystal grain size or deterioration in uniformity of the crystal grain size, depending on the composition of the soft magnetic powder. On the other hand, if the temperature or time of the heat treatment is higher than the upper limit, crystallization is excessively developed, which may result in too large a crystal grain size or deterioration in uniformity of the crystal grain size, depending on the composition of the soft magnetic powder.

[0121] The atmosphere for the crystallization treatment is not particularly limited, but is preferably an inert gas atmosphere such as nitrogen or argon, a reducing gas atmosphere such as hydrogen or ammonia decomposition gas, or a reduced pressure atmosphere thereof. Thus, the metal can be crystallized while suppressing oxidation, and a soft magnetic powder having excellent magnetic properties can be obtained.

[0122] The oxygen concentration of the atmosphere during the crystallization process affects the amount of oxides generated. Therefore, the oxygen concentration of the atmosphere during the crystallization process is preferably set to 1000 ppm or less, more preferably 5 ppm or more and 500 ppm or less, and further preferably 10 ppm or more and 200 ppm or less in terms of volume ratio. This can suppress the generation of oxides and obtain a soft magnetic powder that can produce a high-density powder compact.

[0123] The heating rate in the crystallization treatment is preferably 1°C / min or more and 80°C / min or less, more preferably 2°C / min or more and 30°C / min or less, and further preferably 4°C / min or more and 20°C / min or less. By setting the heating rate within the range, it is easy to suppress the unevenness of the heating rate even when a large amount of metal powder is subjected to crystallization treatment, and it is easy to control the crystal grain size of the soft magnetic powder within the range, and the deviation of the crystal grain size can be suppressed. It should be noted that if the heating rate is lower than the lower limit, the efficiency of the crystallization treatment is reduced, and the manufacturing efficiency of the soft magnetic powder may be reduced. On the other hand, if the heating rate is higher than the upper limit, when a large amount of metal powder is subjected to crystallization treatment, the deviation of the crystal grain size of the soft magnetic powder becomes large, and the coercive force of the soft magnetic powder may increase.

[0124] The cooling rate in the crystallization treatment is not particularly limited, but is preferably 1°C / min or more and 100°C / min or less, more preferably 2°C / min or more and 30°C / min or less, and further preferably 4°C / min or more and 20°C / min or less. By setting the cooling rate within the range, it is easy to control the crystal grain size of the soft magnetic powder within the range. In addition, it is easier to suppress the deviation of the crystal grain size.

[0125] As described above, the soft magnetic powder involved in the present embodiment can be manufactured. In addition, the manufactured soft magnetic powder can also be classified as needed. As a classification method, for example, dry classification such as sieving classification, inertial classification, centrifugal classification, wet classification such as sedimentation classification, etc. can be listed.

[0126] In addition, as required, an insulating film may be formed on the surface of each particle of the obtained soft magnetic powder. As the constituent material of the insulating film, for example, inorganic materials such as phosphates such as magnesium phosphate, calcium phosphate, zinc phosphate, manganese phosphate, and cadmium phosphate, silicates such as sodium silicate, ceramic materials such as silicon oxide, aluminum oxide, magnesium oxide, zirconium oxide, and titanium oxide, glass materials such as borosilicate glass and silica glass, etc. can be cited.

[0127] 3.Powder cores and magnetic components

[0128] Next, the powder magnetic core and the magnetic element according to the embodiment will be described.

[0129] The magnetic element according to the embodiment can be applied to various magnetic elements having a magnetic core, such as a choke coil, an inductor, a noise filter, a reactor, a transformer, a motor, an actuator, a solenoid valve, a generator, etc. In addition, the powder magnetic core according to the embodiment can be applied to the magnetic core of these magnetic elements.

[0130] Below, two types of coil components are described as representative examples of magnetic elements.

[0131] 3.1. Ring type

[0132] First, a ring-shaped coil component as an example of the magnetic element according to the embodiment will be described.

[0133] Figure 2 1 is a plan view schematically showing a ring-shaped coil component 10 .

[0134] Figure 2 The coil component 10 shown includes a ring-shaped powder magnetic core 11 and a conductive wire 12 wound around the powder magnetic core 11 .

[0135] The powdered magnetic core 11 is obtained by supplying a mixture obtained by mixing the soft magnetic powder and the binder involved in the embodiment to a molding die, and then pressurizing and molding. That is, the powdered magnetic core 11 is a powder body containing the soft magnetic powder involved in the embodiment. Such a powdered magnetic core 11 has a high molding density and a high magnetic permeability. Therefore, when the coil component 10 having the powdered magnetic core 11 is mounted on an electronic device, etc., the high performance and miniaturization of the electronic device, etc. can be achieved. It should be noted that the binder can be added as needed or omitted.

[0136] In addition, the coil component 10 as a magnetic element including the powder magnetic core 11 can achieve low loss and miniaturization due to the low coercive force and high magnetic permeability of the powder magnetic core 11 .

[0137] As the constituent material of the binder used for making the powder magnetic core 11, for example, organic materials such as silicone resin, epoxy resin, phenol resin, polyamide resin, polyimide resin, polyphenylene sulfide resin, phosphates such as magnesium phosphate, calcium phosphate, zinc phosphate, manganese phosphate, cadmium phosphate, and silicates such as sodium silicate can be listed, and especially thermosetting polyimide or epoxy resin is preferred. These resin materials are easily cured by heating and have excellent heat resistance. Therefore, the manufacturing ease and heat resistance of the powder magnetic core 11 can be improved.

[0138] In addition, the ratio of the binder to the soft magnetic powder will vary slightly depending on the saturation magnetic flux density, mechanical properties, allowed eddy current loss, etc. of the powder magnetic core 11 to be manufactured, but is preferably 0.5% by mass or more and 5% by mass or less, and more preferably 1% by mass or more and 3% by mass or less. In this way, the particles of the soft magnetic powder can be fully bonded to each other, and the powder magnetic core 11 with excellent magnetic properties such as saturation magnetic flux density and magnetic permeability can be obtained. In the mixture, various additives can also be added according to any purpose as needed.

[0139] The conductive wire 12 may be made of a material having high conductivity, such as a metal material including Cu, Al, Ag, Au, Ni, etc. An insulating film may be provided on the surface of the conductive wire 12 as required.

[0140] It should be noted that the shape of the powder core 11 is not limited to Figure 2 The ring shape shown may be, for example, a shape in which the ring is partially defective, or a shape in which the long side direction is a straight line.

[0141] Furthermore, the powder core 11 may contain a soft magnetic powder other than the soft magnetic powder according to the above-described embodiment and a non-magnetic powder as necessary.

[0142] 3.2. Closed-circuit type

[0143] Next, a closed-circuit type coil component will be described as an example of the magnetic element according to the embodiment.

[0144] Figure 3 It is a perspective view schematically showing a closed-circuit type coil component 20 .

[0145] Next, the closed-circuit type coil component 20 will be described. However, in the following description, the differences from the toroidal type coil component 10 will be mainly described, and descriptions of the same matters will be omitted.

[0146] like Figure 3 As shown, the coil component 20 according to the present embodiment is formed by burying a coil-shaped conductive wire 22 inside a powder core 21. That is, the coil component 20 is formed by molding the conductive wire 22 in the powder core 21. The powder core 21 has the same structure as the powder core 11 described above.

[0147] The coil component 20 of such a form can be easily obtained in a relatively small size. In addition, due to the low coercivity and high magnetic permeability of the powder magnetic core 21, the coil component 20 with low loss and small size can be obtained.

[0148] Furthermore, since the conductive wire 22 is buried inside the powder core 21, a gap is unlikely to be generated between the conductive wire 22 and the powder core 21. Therefore, the vibration of the powder core 21 caused by magnetic bias can be suppressed, and the generation of noise associated with the vibration can also be suppressed.

[0149] It should be noted that, as necessary, the powder core 21 may further include soft magnetic powder or non-magnetic powder other than the soft magnetic powder according to the above-mentioned embodiment.

[0150] 4. Electronic devices

[0151] Next, based on Figures 4 to 6 An electronic device including the magnetic element according to the embodiment will be described.

[0152] Figure 4 It is a perspective view showing the structure of a mobile personal computer 1100 as an electronic device including the magnetic element 1000 according to the embodiment. Figure 4 The personal computer 1100 shown in the figure comprises a main body 1104 having a keyboard 1102 and a display unit 1106 having a display unit 100. The display unit 1106 is rotatably supported by the main body 1104 via a hinge structure. Such a personal computer 1100 has magnetic components 1000 such as a choke coil, an inductor, a motor, etc. for a switching power supply.

[0153] Figure 5 It is a plan view showing the structure of a smartphone 1200 as an electronic device including the magnetic element 1000 according to the embodiment. Figure 5 The smartphone 1200 shown has a plurality of operation buttons 1202, an earpiece 1204, and a mouthpiece 1206. The display unit 100 is disposed between the operation buttons 1202 and the earpiece 1204. Such a smartphone 1200 has magnetic components 1000 such as an inductor, a noise filter, and a motor therein.

[0154] Figure 6 The digital still camera 1300 is a perspective view showing the structure of an electronic device including the magnetic element 1000 according to the embodiment. The digital still camera 1300 generates an imaging signal by photoelectrically converting light and shadow of a subject through an imaging element such as a CCD (Charge Coupled Device).

[0155] Figure 6The digital still camera 1300 shown in the figure has a display unit 100 provided on the back of a housing 1302. The display unit 100 functions as a viewfinder that displays a subject as an electronic image. In addition, a light receiving unit 1304 including an optical prism, a CCD, etc. is provided on the front side of the housing 1302, i.e., the inner side in the figure.

[0156] The photographer checks the subject image displayed on the display unit 100 and presses the shutter button 1306, and the CCD imaging signal at that time is transferred and stored in the memory 1308. Such a digital still camera 1300 may also include a magnetic element 1000 such as an inductor or a noise filter.

[0157] As an electronic device according to an embodiment of the present invention, in addition to Figure 4 Personal computer 1100, Figure 5 Smartphone 1200, Figure 6 In addition to the digital still camera 1300, examples include: mobile phones, tablet terminals, clocks, inkjet ejection devices such as inkjet printers, portable personal computers, televisions, video cameras, video recorders, car navigation devices, pagers, electronic notebooks, electronic dictionaries, calculators, electronic game equipment, word processors, workstations, video phones, anti-theft TV monitors, electronic binoculars, POS terminals, electronic thermometers, blood pressure monitors, blood glucose meters, electrocardiogram measuring devices, ultrasonic diagnostic devices, medical equipment such as electronic endoscopes, fish finders, various measuring equipment, instruments for vehicles, aircraft, and ships, mobile body control equipment such as automobile control equipment, aircraft control equipment, railway vehicle control equipment, and ship control equipment, flight simulators, etc.

[0158] Such an electronic device includes the magnetic element according to the embodiment. Thus, it is possible to enjoy the effects of low loss and small size of the magnetic element and realize power saving and miniaturization of the electronic device.

[0159] 5. Effects of the soft magnetic powder according to the embodiment

[0160] As described above, the soft magnetic powder according to the present embodiment has a composition formula of Fe in terms of atomic ratio as determined by solid emission spectrometry (OES). x Cu a Nb b (Si 1-y (B 1-z Cr z ) y ) 100-x-a-bIndicates that a, b, x, y, and z satisfy 0.3≤a≤2.0, 2.0≤b≤4.0, 75.5≤x≤79.5, 0.55≤y≤0.91, and 0.015≤z≤0.185.

[0161] The soft magnetic powder according to the present embodiment includes an amorphous phase 2 composed of an amorphous structure having Fe as a constituent element with the highest concentration, and a crystalline phase 3 composed of a crystalline structure having Fe as a constituent element with the highest concentration.

[0162] Furthermore, when the Cr content [atomic %] obtained by a solid emission spectrometer (OES) is denoted as X(Cr), and the Cr content [atomic %] and the B content [atomic %] of the amorphous phase 2 obtained by an energy dispersive X-ray fluorescence analyzer (EDX) are denoted as Y(Cr) and Y(B), the soft magnetic powder according to the present embodiment satisfies the following formulas (1) and (2):

[0163] X(Cr)<Y(Cr)≤X(Cr)+1.0 (1),

[0164] 3.0≤Y(B)≤15.0 (2).

[0165] According to such a configuration, due to its excellent oxidation resistance, a soft magnetic powder capable of manufacturing a powder compact having high density and magnetic permeability can be obtained. In addition, the amorphous phase 2 can be stabilized, and the coarsening of the crystalline phase 3 during the crystallization treatment can be suppressed regardless of the heat treatment conditions, so that a soft magnetic powder having low coercivity and being easy to manufacture can be obtained.

[0166] In addition, when the Cr content (atomic %) of the crystal phase 3 of the soft magnetic powder according to the present embodiment determined by an energy dispersive X-ray fluorescence analyzer (EDX) is defined as Z(Cr), it is preferred that the following formula (3) is satisfied:

[0167] Z(Cr)<X(Cr) (3),

[0168] In addition, the B content Y(B) [atomic %] of the amorphous phase 2 of the soft magnetic powder according to the present embodiment determined by an energy dispersive X-ray fluorescence analyzer (EDX) preferably satisfies the following formula (4):

[0169] 3.0≤Y(B)≤10.0 (4).

[0170] According to such a configuration, the Cr content Z (Cr) of the crystal phase 3 and the B content Y (B) of the amorphous phase 2 are optimized, respectively, so that the amorphous phase 2 can be further stabilized.

[0171] In addition, Y(Cr) [atomic %], Y(B) [atomic %] and Cr content Z(Cr) [atomic %] preferably satisfy the following formula (5) to formula (7):

[0172] 1.5≤Y(Cr)≤2.5 (5),

[0173] 4.0≤Y(B)≤7.0 (6),

[0174] 0.8≤Z(Cr)≤2.0 (7).

[0175] According to such a configuration, the Cr content and the B content of the amorphous phase 2 and the Cr content of the crystalline phase 3 are optimized, respectively, so that the amorphous phase 2 can be further stabilized.

[0176] The oxygen content of the soft magnetic powder is preferably 1500 ppm or less. This can suppress the generation of oxides that cause a decrease in the density of the green compact to a particularly low level.

[0177] Furthermore, the powder magnetic core according to the embodiment includes the soft magnetic powder according to the embodiment, thereby obtaining a powder magnetic core having low coercivity and high magnetic permeability.

[0178] Furthermore, the magnetic element according to the embodiment includes the powder magnetic core according to the embodiment. Thus, a magnetic element that achieves low loss and miniaturization can be obtained.

[0179] Furthermore, the electronic device according to the embodiment includes the magnetic element according to the embodiment, thereby achieving power saving and miniaturization of the electronic device.

[0180] As mentioned above, the soft magnetic powder, the powder magnetic core, the magnetic element, and the electronic device of the present invention have been described based on the preferred embodiments, but the present invention is not limited thereto.

[0181] For example, in the embodiment, a compressed powder body such as a compressed powder core is listed as an example of the use of the soft magnetic powder of the present invention, but the use example is not limited to this. For example, it can also be a magnetic device such as a magnetic fluid, a magnetic viscoelastic elastomer composition, a magnetic head, an electromagnetic wave shielding component, a motor, a magnetic core of a generator, etc.

[0182] Furthermore, the soft magnetic powder, powder magnetic core, magnetic element, and electronic device of the present invention may have arbitrary components added to the above-described embodiments.

[0183] Furthermore, the shapes of the powder magnetic core and the magnetic element are not limited to the shapes shown in the drawings, but may be any shapes.

[0184] Example

[0185] Next, specific examples of the present invention will be described.

[0186] 6. Manufacturing of powder compacts

[0187] 6.1. Sample No.1

[0188] First, the raw materials are melted in a high-frequency induction furnace and powdered by a rotary water jet atomization method to obtain metal powder.

[0189] Next, the obtained metal powder was subjected to a crystallization treatment by heating in a nitrogen atmosphere. Thus, a soft magnetic powder was obtained. The heating temperature and the heating rate in the crystallization treatment are shown in Table 1. In addition, the cooling rate after heating was 10°C / min. It should be noted that the heating temperatures shown in Table 1 are values ​​obtained by previously exploring the heating temperatures at which the coercive force of each soft magnetic powder becomes extremely small.

[0190] Next, the soft magnetic powder was classified by a wind classifier. Then, the soft magnetic powder after classification was subjected to composition analysis using a solid emission spectrometer (OES). The analysis results are shown in Table 1.

[0191] Next, the particle size distribution of the obtained soft magnetic powder was measured. Then, when the average particle size of the soft magnetic powder was obtained from the particle size distribution, the average particle size of the soft magnetic powder was 20 μm.

[0192] Next, the obtained soft magnetic powder was mixed with epoxy resin as a binder to obtain a mixture. The amount of epoxy resin added was 2 parts by mass (2% by mass of the soft magnetic powder) per 100 parts by mass of the soft magnetic powder.

[0193] Next, the obtained mixture was stirred and then dried for a short time to obtain a block-shaped dry body. Next, the dry body was passed through a sieve with a mesh size of 600 μm and then pulverized to obtain a granulated powder. The obtained granulated powder was dried at 50° C. for 1 hour.

[0194] Next, the obtained granulated powder is filled in a molding die, and molding is performed under the following molding conditions, and the binder is solidified under the following solidification conditions to obtain a green compact.

[0195] Molding conditions

[0196] Molding method: pressure molding

[0197] Shape of pressed powder: Ring

[0198] ·Powder pressing size: outer diameter 14mm, inner diameter 8mm, thickness 3mm

[0199] Molding pressure: 3t / cm2 (294MPa)

[0200] Curing conditions of adhesive

[0201] Heating temperature: 150℃

[0202] Heating time: 0.5 hours

[0203] Heating atmosphere: air

[0204] 6.2. Sample No. 2 to 21

[0205] Except that the production conditions of the soft magnetic powder were changed as shown in Table 1 or Table 2, a soft magnetic powder and a green compact were obtained in the same manner as Sample No. 1.

[0206] [Table 1]

[0207]

[0208] [Table 2]

[0209]

[0210] In addition, in Table 1 and Table 2, among the soft magnetic powders of each sample No., those corresponding to the present invention are referred to as "Examples", and those not corresponding to the present invention are referred to as "Comparative Examples".

[0211] 7. Evaluation of soft magnetic powder and powder compact (powder core)

[0212] 7.1. Crystalline particle size of soft magnetic powder

[0213] The crystal particle size of the soft magnetic powder of each example and each comparative example was measured by X-ray diffraction.

[0214] 7.2. Oxygen content of soft magnetic powder

[0215] The oxygen content of the soft magnetic powder of each example and each comparative example was measured. The oxygen content was measured using an oxygen-nitrogen-hydrogen analyzer, ONH836, manufactured by LECO. The measurement results are shown in Tables 3 and 4.

[0216] 7.3. Density of powder compact

[0217] The density of the green compact produced using the soft magnetic powder of each example and each comparative example was measured. The density of the green compact was evaluated according to the following evaluation criteria. The measurement results are shown in Tables 3 and 4.

[0218] A: The density of the powder compact is 5.01 g / cm 3 above

[0219] B: The density of the powder compact is 4.99 g / cm 3 Above and less than 5.01g / cm 3

[0220] C: The density of the powder body is less than 4.99g / cm 3

[0221] 7.4. Coercivity of soft magnetic powders

[0222] The coercive force of the soft magnetic powder of each example and each comparative example was measured. Then, the measured coercive force was evaluated according to the following evaluation criteria. The evaluation results are shown in Tables 3 and 4.

[0223] A: Coercivity is less than 0.90Oe

[0224] B: Coercive force is 0.90 Oe or more and less than 1.33 Oe

[0225] C: Coercivity is 1.33 Oe or more and less than 1.67 Oe

[0226] D: Coercive force is 1.67 Oe or more and less than 2.00 Oe

[0227] E: Coercive force is 2.00 Oe or more and less than 2.33 Oe

[0228] F: Coercivity is 2.33Oe or more

[0229] 7.5. Saturation flux density of soft magnetic powder

[0230] The saturation magnetic flux density of each soft magnetic powder obtained in each Example and each Comparative Example was calculated. The calculation results are shown in Tables 3 and 4.

[0231] 7.6. Magnetic permeability of powder compacts

[0232] The magnetic permeability of the green compact produced using the soft magnetic powder obtained in each Example and each Comparative Example was measured.

[0233] In Tables 3 and 4, among the soft magnetic powders of each sample No., those corresponding to the present invention are shown as “Examples”, and those not corresponding to the present invention are shown as “Comparative Examples”.

[0234] [Table 3]

[0235]

[0236] [Table 4]

[0237]

[0238] As can be seen from Tables 3 and 4, the soft magnetic powders of each example have excellent oxidation resistance and low oxygen content even when the Fe content is high. In addition, the compacts produced using the soft magnetic powders of each example have high density and magnetic permeability. Moreover, the soft magnetic powders of each example have low coercivity regardless of the heating rate.

[0239] From the above results, it was confirmed that according to the present invention, a green compact having high density and magnetic permeability can be produced, and a soft magnetic powder having low coercive force and being easy to produce can be produced.

[0240] It should be noted that the same results as those in the above examples were obtained with a soft magnetic powder having the same structure as in the above examples except that the water atomization method was used instead of the rotating water flow atomization method.

Claims

1. A soft magnetic powder, characterized in that: The composition of the soft magnetic powder obtained by solid emission spectrometry (OES) is represented by the composition formula in terms of atomic ratio: x Cu a Nb b (Si 1-y (B 1-z Cr z ) y ) 100-x-a-b Indicates that a, b, x, y, and z satisfy 0.3≤a≤2.0, 2.0≤b≤4.0, 75.5≤x≤79.5, 0.55≤y≤0.91, and 0.015≤z≤0.

185. The soft magnetic powder has an amorphous phase and a crystalline phase, the amorphous phase is composed of an amorphous structure in which Fe is the highest concentration of the constituent element, and the crystalline phase is composed of a crystalline structure in which Fe is the highest concentration of the constituent element, When the Cr content in atomic % determined by a solid-state emission spectrometer (OES) is denoted as X(Cr), and the Cr content in atomic % and the B content in atomic % of the amorphous phase determined by an energy dispersive X-ray fluorescence analyzer (EDX) are denoted as Y(Cr) and Y(B), the following equations (1) and (2) are satisfied: X(Cr)<Y(Cr)≤X(Cr)+1.0 (1), 3.0≤Y(B)≤15.0 (2).

2. The soft magnetic powder according to claim 1, characterized in that When the Cr content in atomic % of the crystal phase determined by an energy dispersive X-ray fluorescence analyzer (EDX) is defined as Z(Cr), the following formula (3) is satisfied: Z(Cr)<X(Cr) (3), The B content Y(B) in the amorphous phase in atomic % determined by an energy dispersive X-ray fluorescence analyzer (EDX) satisfies the following formula (4): 3.0≤Y(B)≤10.0 (4).

3. The soft magnetic powder according to claim 2, characterized in that The Y(Cr) in atomic %, the Y(B) in atomic % and the Z(Cr) in atomic % satisfy the following formulas (5) to (7), 1.5≤Y(Cr)≤2.5 (5), 4.0≤Y(B)≤7.0 (6), 0.8≤Z(Cr)≤2.0 (7).

4. The soft magnetic powder according to any one of claims 1 to 3, characterized in that The oxygen content of the soft magnetic powder is 1500 ppm or less.

5. A powder magnetic core, characterized in that: The invention comprises the soft magnetic powder according to any one of claims 1 to 4.

6. A magnetic element, characterized in that: A powder magnetic core according to claim 5 is provided.

7. An electronic device, characterized in that: A magnetic element according to claim 6.

Citation Information

Patent Citations

  • Soft magnetic powder, dust core, magnetic element and electronic device

    JP2019189928A